Hypoglycemia and decreased insulin requirement caused by malignant insulinoma in a type 1 diabetic patient: when the hoof beats are from a zebra, not a horse. Issue 6 (6th April 2017) - Gjelberg, Hilde K.; Hoem, Dag; Verbeke, Caroline S.; Eide, Johan; Cooper, John G.; Molven, Anders
Key Clinical Message: Insulinomas are uncommon tumors, and in patients with diabetes mellitus they are extremely rare. We describe a patient with type 1 diabetes who developed malignant insulinoma. When hypoglycemic episodes persist in a patient with diabetes and treatment‐induced and other causes of hypoglycemia have been ruled out, an insulin‐producing tumor should be considered. Abstract : Insulinomas are uncommon tumors, and in patients with diabetes mellitus they are extremely rare. We describe a patient with type 1 diabetes who developed malignant insulinoma. When hypoglycemic episodes persist in a patient with diabetes and treatment‐induced and other causes of hypoglycemia have been ruled out, an insulin‐producing tumor should be considered.